Non-specialized means of causative semantics expression in the Slavic and Germanic languages (based on the lexical semantic group of defense and protection) - A.H. Litvinovich (Ученые записки Казанского университета: Серия Гуманитарные науки)
The paper deals with the peculiarities of verbs that convey causative semantics without being specialized for it. The objective of the research is to identify the specific features of Slavic (Russian, Belarusian) and Germanic (English, German) defense and protection verbs with regard to causativity. The study of lexical semantic groups in the aspect of causativity is topical, because it contributes to the specification of causativity as a category. It works towards resolving a controversial causativity theory issue about the scope and boundaries of causative verbs class, as well as helps to reveal some internal laws of the causative category development (gradual nature of the causative category). The following methods were used: contextual, transformational, comparative methods; dictionary definitions analysis, component and distributive analysis. It was found that defense and protection verbs in three (Russian, Belarusian, German) of the four studied languages have units that do not contain a causative component. Within the analyzed lexical semantic group, there are verbs with a high and low degree of causativity (vertical changes of causativity degree). In these two groups, it is possible to identify the units that are able and unable to change the causativity degree in a context (horizontal changes of causativity degree). The gradual character of causativity is an integral feature of the studied Slavic and Germanic verbs. The degree of causativity is their differential trait.